Precipitation of high-quality multilayer-graphene using Al2O3 barrier and Au cap layers. Issue 1786 (26th August 2015) - Yamada, Jumpei; Suzuki, Manabu; Ueda, Yuki; Maruyama, Takahiro; Naritsuka, Shigeya
ABSTRACT: The mechanism for the precipitation of multilayer graphene was investigated with respect to the use of an Al2 O3 barrier layer and Au capping layer. The Al2 O3 barrier layer suppresses the dissolution of carbon into the catalyst, especially at low temperature, and assists a decrease in the density of graphene nuclei. On the other hand, the Au capping layer is beneficial to weaken the strong binding between the catalyst and the graphene carbon atoms, and enhances the surface migration of precipitated carbon adatoms. A combination of the Al2 O3 barrier layer and Au capping layer is useful for the synthesis of high-quality graphene with large grains. On a sample with both layers annealed for 60 min, the area of 5-layer graphene islands is as large as 10 μm, and covers 60% of the entire surface. The Raman D/G band intensity ratio of 0.024 indicates the precipitated graphene is high quality.